Concurrent and Subsequent Associations Between Daily Digital Technology Use and High‐Risk Adolescents' Mental Health Symptoms. Issue 1 (3rd May 2017) - George, Madeleine J.; Russell, Michael A.; Piontak, Joy R.; Odgers, Candice L.
Abstract : Adolescents are spending an unprecedented amount of time using digital technologies (especially mobile technologies), and there are concerns that adolescents' constant connectivity is associated with poor mental health, particularly among at‐risk adolescents. Participants included 151 adolescents at risk for mental health problems ( M age = 13.1) who completed a baseline assessment, 30‐day ecological momentary assessment, and 18 month follow‐up assessment. Results from multilevel regression models showed that daily reports of both time spent using digital technologies and the number of text messages sent were associated with increased same‐day attention deficit hyperactivity disorder (ADHD) and conduct disorder (CD) symptoms. Adolescents' reported digital technology usage and text messaging across the ecological momentary assessment (EMA) period was also associated with poorer self‐regulation and increases in conduct problem symptoms between the baseline and follow‐up assessments. Abstract : The title for this Special Section isContemporary Mobile Technology and Child and Adolescent Development, edited by Zheng Yan and Lennart Hardell